Perbandingan Pembelajaran Daring dengan Video dan Zoom Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi - Rahayu, Sri; Amri, Fahimul (Jurnal Simki Pedagogia, 2021)
The purpose of this study is to determine the difference between online learning with video and online learning with zoom so that it can determine which learning media is more suitable and most able to increase student activity in economics subjects, which aims to make learning not monotonous. Data collection techniques used by researchers include documentation, tests, and observations. The test uses cognitive and skill tests. From the results of data processing, it can be concluded that there are differences in cognitive and psychomotor assessment of online learning with video and online learning with zoom on economic subjects. It can be seen from the results of parametric statistical testing shows that sig. (2-tailed) < 0.05. For cognitive aspects 0.002 < 0.05 and psychomotor aspects 0.024 < 0.05. Online learning with video is better than online learning with zoom on economic subjects, both cognitive and psychomotor aspects. This can be seen from the average cognitive value of online learning with video of 67.08 and online learning with zoom of 55.19. The psychomotor aspect also shows the same thing for the average value of online learning with video which is higher than online learning with zoom, namely 83.42 and 77.41.